PLANNING AND DESIGNING ESPORTS TRAINING CENTER WITH FUTURISTIC ARCHITECTURE APPROACH - Bahri, Alif Sirajuddin; Bahri, Samsul (Journal of Architectural Design and Development (JAD), 2024)
Advances in the field of information and communication technology are one of the leapfrogging products of the industrial revolution 4.0 to reap high efficiency and profits. Esports is a type of achievement sport that uses online video games as a medium for its implementation. Various sports party activities, regional, national, and international, have made esports part of the competition.  This research aims to get a visually modern building design, equipped with the latest technology in the facilities. The design method uses a futuristic architectural theme approach in line with the context of South Jakarta as a metropolitan city. There are two building masses, the office mass with four floors and the tower mass with ten floors. The different height level on the façade is an implementation of the futuristic architecture and illustrates the different levels of levels in esports. The aesthetic shape of the façade is displayed with a different design from the surroundings which illustrates that esports is an aesthetic sport and is different from other types of sports. The façade with the shape of longitudinal bent lines, translated as motion and speed illustrates that esports requires the fine motor skills of its players. The façade with white and gray ACP material illustrates the honesty of the material and the appearance of innocent characters as a form of sportsmanship behavior of esports players in matches. The combination of ACP material, laminated glass, and curtain wall frame reflects the practical use of building materials and minimizes pollution to the environment.